Psycho-sociolinguistic Analysis in Arabic Linguistics: A Theoritical Study - As’ad, Zidan; Aditya Akmal Zamanil Yahya; Anjaz; Ach. Jawahir (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This study aims to analyze the role of psycho-sociolinguistics in the Arabic language through a literature review. Psycho-sociolinguistics is one of the branches of linguistics that focuses on the relationship between language and the psychology and sociology of native speakers of a language. This study uses a qualitative approach by analyzing data from various relevant literary sources. The results of the study show that psycho-sociolinguistics helps to understand the role of psychological and social factors in the process of using the Arabic language. This study also emphasizes the importance of understanding the differences between dialects, grammar, and social context in communication. The results of this study are used as a basis for the development of more effective communication strategies in language education.